Genetics meets metabolomics from experiment to systems biology - Suhre, Karsten. (Springer New York :, 2012)
Unlike previous books published on metabolomics, this book switches the focus from experimental questions and technical challenges, to the application of metabolomics with an emphasis on the underlying genetics. The chapters provide a thorough basis for the understanding of the underlying experimental techniques, concepts and potential biomedical applications of this exciting field. The interdisciplinary approach of this book addresses a wide readership, and contains educational aids for anyone not familiar with a particular area of metabolomics. The area of research where genetics and metabolomics meet is likely to represent a field where systems biology shall prosper highly in the years to come. Introduction -- Pre-conditions for high quality biobanking in large human epidemiological cohorts for metabolomics and other -omics studies -- Assay tools for metabolomics -- Statistical methods in genetic and molecular epidemiology and their application in studies with metabolic phenotypes -- Ultrahigh resolution mass spectrometry based non-targeted microbial metabolomics -- etabolomic systems biology of protozoan parasites -- Mouse genetics and metabolic mouse phenotyping -- Metabolomics in animal breeding -- Metabolomics applications in human nutrition -- Metabolomics for the individualized therapy of androgen deficiency syndrome in male adults -- Systems biology resources arising from the human metabolome project -- Understanding cancer metabolism through global metabolomics -- Genetic and metabolic determinants of fatty acid chain length and desaturation, their incorporation into lipid classes and their effects on risk of vascular and metabolic disease -- Mapping metabolomic quantitative trait loci (mQTL) – A link between metabolome-wide association studies and systems biology -- Metabolic traits as intermediate phenotype -- Genome-wide association studies with metabolomics -- Systems biology meets metabolism -- Index.